(untitled) - Satzinger, John W (Canada, 2001)
This concise text introduced the object-oriented revolution to higher education when it was first published in 1996. Now the authors have created the revised second edition to conform to the Unified Modeling Language (UML) standard. In addition to its usefulness in systems analysis and design areas, the text functions as an introduction to object-oriented programming by introducing Java. The clean, straightforward style of this text in its first edition garnered rave reviews from pioneers of the object-oriented movement. Now that OO is entering the mainstream, you'll appreciate this short but effective introduction to object oriented methods' core concepts and advantages.
Ngôn ngữ mô hình hóa
Keywords: Object-oriented programming,Computer science,Lập trình hướng đối tượng,Khoa học máy tính